Helping parents to help children overcome fear: The influence of a short video tutorial. (7th August 2019) - Ewing, Donna; Pike, Alison; Dash, Suzanne; Hughes, Zoe; Thompson, Ellen Jo; Hazell, Cassie; Ang, Chian Mei; Kucuk, Nesya; Laine, Amie; Cartwright‐Hatton, Sam
Abstract : Objectives: Anxiety runs in families, and its transmission is largely environmental. However, studies rarely explore this process in clinically anxious parents or ask participants to face a genuine fear. We also do not know whether this process is modifiable. This study will explore these questions using a sample of clinically anxious parents. Design: Experimental design comparing clinically anxious parents with non‐anxious parents, and exploring the effects of a tutorial intervention versus a control group. Methods: Parents with and without anxiety disorders and their children (5–9 years) participated ( N = 72). Children chose two fearful animal stimuli. Parents helped the child approach the first in graded steps. The following parental behaviours were recorded: positive/negative verbal information; positive/negative modelling; encouragement/praising of approach/avoidance behaviours. Half the parents were then randomly assigned to a short video tutorial advising how to help children cope with fearful situations. The remainder watched a control video. The approach task was repeated with the second stimulus. Results: Parenting behaviours fell into two categories: 'approach parenting' (encouraging/praising/modelling approach; positive verbal information) and 'avoidance parenting' (encouraging/praising/modelling avoidance; negative verbal information). The parenting tutorial increased 'approach parenting' and decreased 'avoidance parenting' and was associated with increased child approach towards fearful stimuli. This was not moderated by parent or child anxiety. Conclusions: Parenting, particularly 'avoidance parenting', is associated with children's approach and avoidance. A short video tutorial modified these parenting behaviours and reduced avoidance. These effects were apparent regardless of parent or child anxiety level. Practitioner points: Avoidance and approach parenting may influence children's response to fearful stimuli. Avoidance parenting may be more problematic than lack of approach parenting. Approach and avoidance parenting are amenable to manipulation by short video tutorial. Parenting improvement resulted in increased approach behaviour in children.